أحكام رياضة الكاراتيه في الشريعة الإسلامية - مسعي عون, حسين; محده, الأخضر (University of Eloued-جامعة الوادي, 2022)
" ملخص عنوان المذكرة الموسوم: بـ ""أحكام رياضة الكاراتيه في الشريعة الإسلامية""، وإشكاليته الرئيسية التي حاولنا الإجابة عنها، والتي تتمحور حول أحكام رياضة الكاراتيه وبعض القواعد المنظمة للعبة. وقد جاء الموضوع في مبحثين: حيث تطرقنا في المبحث الأول لتعريف رياضة الكاراتيه ونشأتها وتطورها، وذكر مشروعيتها وآراء الفقهاء فيها، كما أوردنا الضوابط الخاصة بهذه الرياضة، وجعل المبحث الثاني لمقاصد رياضة الكاراتيه والأحكام الخاصة بها؛ من حكم التحية والأقوال التي يتلفظ بها، وكذلك حكم الضرب المسموح به في قانون اللعبة. ومن النتائج الأساسية التي وصل إليها البحث في هذا الموضوع أن رياضة الكاراتيه من الرياضات المشروعة التي حث الإسلام على ممارستها، وجعلها من الأعمال الفاضلة؛ إذا اقترنت بنية صالحة، شريطة ألا تتعارض مع الضوابط والأحكام الشرعية، وكذلك القوانين المنظمة للعبة الموافقة للشريعة. واقترح البحث ضرورة تهذيب القوانين المنظمة للعبة في ديار الإسلام؛ حتى لا تتعارض مع أحكام الشريعة. ""Abstract The title of the memorandum marked: “The provisions of Karate in the Islamic Sharia,” and its main problem that we tried to answer, which revolves around the provisions of Karate and some of the rules governing the game. The subject came in two sections: where we discussed in the first section the definition of the sport of Karate, its origins and development, and mentioned its legitimacy and the opinions of jurists in it. From the rule of greeting and sayings uttered, as well as the rule of beating allowed in the law of the game. Among the main results reached by the research on this subject is that karate is one of the legitimate sports that Islam urged to practice, and made it one of the virtuous deeds; If it is accompanied by a valid intent, provided that it does not conflict with the legal rulings, as well as the laws regulating the game that are in accordance with the Sharia. The research suggested the necessity of refining the laws regulating the game in the lands of Islam; So as not to conflict with the provisions of Sharia."
مذكرة ماستر
Keywords: رياضة الكاراتيه,حفظ الدين , حكم الضرب , حفظ النفس; Karate, preserving religion, batting rule, self-preservation